Pacific Studies: Quo Vadis? - Anne Holden Rønning (Coolabah, 2014)
Looking back to the past this paper discusses why Pacific studies and in particular Australasian studies became an area of interest in tertiary education in Europe. What subject areas initiated these studies, and how do past legacies shape the present? With cutbacks in higher education over the past two decades the future of interdisciplinary studies and the humanities looks bleak. At the same time due to global business and increased political communication across borders there is a vibrant interest in and need for such studies among businesses and students. For most Europeans the literature of settler countries, with their European legacy, makes access to ways of thought and culture easier than studies of countries with other mythological backgrounds. In today’s multicultural environment such studies can provide knowledge for an understanding of other cultures and increase tolerance of the ‘other’. Area studies have relevance to our situation in Europe with increased migrancy, not least as a result of Schengen and EU regulations.